Hungarian general practice paediatricians’ antibiotic prescribing behaviour for suspected respiratory tract infections: a qualitative study - Ria Benkő; Mária Matuz; Ketevan Kandelaki; Balázs Babarczy; Ágnes Hajdu; Renáta Papp; Pantelis Antoniou; Danilo Lo Fo Wong; Sahil Khan Warsi (BMJ Open)
Objectives Inappropriate antibiotic prescribing is a major cause of antimicrobial resistance (AMR). The aim of this study was to explore paediatric general practitioners’ (GP Peds) antibiotic prescription practice in suspected respiratory tract infections (RTIs), using the capability–opportunity–motivation–behaviour framework.Design The design is a qualitative study based on individual, semistructured telephone or virtual interviews.Setting Paediatric general practice in Hungary. We applied stratified maximum variation sampling to cover the categories of age, sex and geographical location of participants.Participants We interviewed 22 GP Peds. Nine were male and 13 were female: 2 of them were less than 40 years old, 14 were between 40 and 60 years, and 6 were above 60 years. 10 worked in low-antibiotic prescription areas, 5 in areas with medium levels of antibiotic prescription, 3 in high-antibiotic prescription areas, and 4 in and around the capital city.Results Study participants had varying antibiotic prescription preferences. Personal experience and physical examination play a central role in GP Peds’ diagnostic and treatment practice. Participants emphasised the need to treat children in their entirety, taking their personal medical record, social background and sometimes parents’ preferences into account, besides the acute clinical manifestation of RTI. Most respondents were confident they apply the most effective therapy even if, in some cases, this meant prescribing medicines with a higher chance of contributing to the development of AMR. Some participants felt antibiotic prescription frequency has decreased in recent years.Conclusions Our findings suggest that a more prudent attitude toward antibiotic prescribing may have become more common but also highlight relevant gaps in both physicians’ and public knowledge of antibiotics and AMR. To reinforce awareness and close remaining gaps, Hungary should adopt its national AMR National Action Plan and further increase its efforts towards active professional communication and feedback for primary care physicians.